The Effect of Dead-end trench on Disease Attacks on Robusta Coffee Plants (Coffea robusta L.) - Rizqi Ramadhan; Canggih Nailil Maghfiroh (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Indonesian is the fourth largest coffee producer in the world. Increased coffee production is subject to proper land control. The use of dead-end trench is useful for accommodating organic matter and biological elements. This study aims to explore the effect of dead-end trench and without dead-end trench application on the attack of leaf rust and leaf spot disease. This research was conducted using qualitative methods by collecting data through observation and weekly observation. The results showed that the use of dead-end trench and without dead-end trench had an effect on the intensity of attacks including: (1) Leaf rust attacks on plants using dead-end trench (R1) of 40.11 and leaf spot of 50.11. The without dead-end trench coffee growing culture (R2) received 35.39 leaf rust attacks and 53.11 leaf spot attacks, (2) leaf rust attacks in the second week reached 40.56 and leaf spot by 51.61. Planting without dead-end trench reached an intensity of leaf rust attacks reaching 37.28 and leaf spot of 53.88, (3) the third week of attacks on planting with a dead-end trench of 40.67 and leaf spot reaching 50.67. Meanwhile, planting without dead-end trench leaf rust attack reached 42.22 and leaf spot by 53.33, (4) the fourth week of planting without dead-end trench increased by 42.56 and leaf spot by 52.61. Plant with dead-end trench reaches 42.50 and leaf spot infestation reaches 50.22. This research makes an important contribution to coffee farmers regarding the use of dead-end trench as an effective minimizing tool in reducing the spread of leaf rust and leaf spot.